PENGARUH INTELLECTUAL CAPITAL TERHADAP KINERJA KEUANGAN PADA PERUSAHAAN PROPERTY DAN REAL ESTATE - Indra Gunawan Siregar; Basuki Basuki; Dede Sunaryo (Universitas Muhammadiyah Tangerang, 2019)
This study aims to examine and analyze the influence of intellectual capital on financialperformance. The design of this study uses explanatory causality design. The population usedin this study is a company listed on the IDX specifically the property and real estate sector forthe period 2012-2017. The analysis method uses multiple linear regression analysis and dataanalysis. The sample selection technique uses purposive sampling.The results of this study partially show that VACA, VAHU variables influence financialperformance (ROA). Whereas STVA and marketing expenses have no effect on financialperformance (ROA). Simultaneously it proved to have an effect on financial performance. Thefindings of this study are the ability of companies to manage efficiently and effectively existingresources, and respond well to the market.Keywords: Intellectual Capital, Marketing Expenses and ROA